Efek toksisitas ekstrak bromelin buah nanas (Ananas comosus L.) dengan metode Brine Shrimp Lethality Test (BSLT) - Betty Fitriyasti; Salmi Salmi (Department of Biology, Faculty of Agriculture, Fisheries and Biology, University of Bangka Belitung, 2021)
Bromelain is proteolytic enzyme extracted from pinepple (Ananas commosus L.) and potents as anticancer. The aimed of this study was to determined the toxicity effect of bromelain extract from pineapple fruit (Ananas commosus L) with brine shrimp lethality test (BSLT) methods. Crude extract of bromelain was obtained by addition of natrium acetat buffer pH 6.5 to pineapple fruit and was setrifugated with 3500 rpm of speed. Bromelain toxiciy was determined by incubated 15 artemia salina Leach (48 aged old) in various concentration of bromelain extract; 3.000 ppm, 2.000 ppm, 1.500 ppm, 1.000 ppm, 500 ppm and 0 ppm for 24 hours. At the end of incubation period, mortality percentages and LC50 were calculated. The result shown that there were increased in mortality percentage as bromelain concentration increased. LC50 value of bromelain exctract was 9.000 ppm. This value indicated that bromelain extract from pineapple fruit had low toxicity effect since its LC50 value were under 1000 ppm. Inconclusion, crude bromelain extract from pineapple fruit did not show anticancer potential based on this study.